2022
DOI: 10.3390/v14122773
|View full text |Cite
|
Sign up to set email alerts
|

Defective Interfering Particles of Influenza Virus and Their Characteristics, Impacts, and Use in Vaccines and Antiviral Strategies: A Systematic Review

Abstract: Defective interfering particles (DIPs) are particles containing defective viral genomes (DVGs) generated during viral replication. DIPs have been found in various RNA viruses, especially in influenza viruses. Evidence indicates that DIPs interfere with the replication and encapsulation of wild-type viruses, namely standard viruses (STVs) that contain full-length viral genomes. DIPs may also activate the innate immune response by stimulating interferon synthesis. In this review, the underlying generation mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Influenza viral genome segments have known variation in their propensity to generate defective viral genomes. In particular, the polymerase complex genes (PB2, PB1, and PA) are known to generate most of the DelVGs in a given influenza infection (Saira, 2013; Wu, 2022). Thus, made linear mixed models for each segment, separating into strain specific models, if strain was found to be a significant predictor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza viral genome segments have known variation in their propensity to generate defective viral genomes. In particular, the polymerase complex genes (PB2, PB1, and PA) are known to generate most of the DelVGs in a given influenza infection (Saira, 2013; Wu, 2022). Thus, made linear mixed models for each segment, separating into strain specific models, if strain was found to be a significant predictor.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 – 30% of virions can propagate fully from cell to cell (Brooke, 2013; Brooke, 2017; Diefenbacher, 2018). While there are a variety of reasons why virions are not fully infectious—for example, SNPs or faulty protein expression—virions harboring genome segments with internal sequence deletions (Davis, 1980; Nayak, 1982; Saira, 2013) have been termed defective interfering particles (DIP) when their accumulation by de novo or exogenous means diminishes the productivity of Influenza A infections and leads to mild disease outcomes; a phenomenon termed defective interference (Dimmock, 2014; Manzoni, 2018; Vignuzi, 2019; Wu, 2022). These defective interfering particles do not produce the proteins necessary for a single DIP to complete an infection, leading to a non-propagative infection that relies on virus coinfection to disseminate (Yamagata, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of other virus infections such as dengue virus, Zika virus, yellow fever virus respiratory syncytial virus, and influenza A virus showed that DIP treatment of human target cells inhibited virus production via activation of cellular innate immunity, which included interferon-dependent antiviral responses. Future direction of DIP-integrating mathematical modeling should incorporate a broad spectrum of virus-host interaction processes in order to robustly quantify and predict the function which the DIPs could have in vaccines, modulation of viral disease, innate immune responses, virus persistence, and virus evolution [68,69]. Although the DIPs offer a novel approach to antiviral therapy, the efforts to translate the in vitro studies to in vivo models are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…One such option is the use of defective interfering particles (DIPs) [ 22 , 23 , 24 , 25 ]. DIPs are naturally arising viral mutants that are found in a variety of RNA viruses [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], including influenza A viruses (IAV) [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Conventional IAV DIPs have a large internal deletion in one of their eight viral RNA (vRNA) segments, leading to a defect in virus replication.…”
Section: Introductionmentioning
confidence: 99%